2009
DOI: 10.1179/136485909x435111
|View full text |Cite
|
Sign up to set email alerts
|

Crude extracts of, and purified compounds from,Pterocarpus angolensis, and the essential oil ofLippia javanica: their in-vitro cytotoxicities and activities against selected bacteria andEntamoeba histolytica

Abstract: In a recent study, various extracts of Pterocarpus angolensis were prepared and tested against bacteria. The acetone extract was found to be the most active against all the bacteria investigated, with minimum inhibitory concentrations varying from 0.0156 mg/ml against Staphylococcus aureus to 2 mg/ml against Enterobacter cloacae. Seven pure compounds were subsequently isolated from the ethanol extract of P. angolensis. Using several chromatographic and spectroscopic methods, the structures of five of these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…A. niger was insensitive to most of the plant extracts with two, only showing an MIC=2.5 mg/ml. These results tend to be supported by similar findings by other reporters 2,3,[8][9][10][11]14,17,20 . In general, the results however, show greater activity by the root extract over the leaf, fruit or stem bark extract.…”
Section: Resultssupporting
confidence: 81%
“…A. niger was insensitive to most of the plant extracts with two, only showing an MIC=2.5 mg/ml. These results tend to be supported by similar findings by other reporters 2,3,[8][9][10][11]14,17,20 . In general, the results however, show greater activity by the root extract over the leaf, fruit or stem bark extract.…”
Section: Resultssupporting
confidence: 81%
“…to treat diarrhea, heavy menstruation, nose bleeding, headache, stomach-ache, parasitic worms, sores and skin problems (Takawira-Nyenya, 2005). Pharmacological studies on P. angolensis revealed antibacterial activity of seeds (Steenkamp et al, 2004), stem bark, roots and leaf extracts (Luseba et al, 2007;Mulaudzi et al, 2011;Samie et al, 2009) and antifungal activity of leaf and bark extracts (Mulaudzi et al, 2011). The latter also showed HIV-1 reverse transcriptase inhibitory activity (Mulaudzi et al, 2011) as well as anthelmintic effects (McGaw et al, 2007;Molgaard et al, 2001).…”
Section: Pterocarpus Angolensismentioning
confidence: 99%
“…Anti-inflammatory activity was also detected in stem bark extracts . Samie et al (2009) demonstrated the presence of epichatechin and derivatives (with strong antibacterial activities but generally weak activities against Entamoeba histolytica) in stem barks.…”
Section: Pterocarpus Angolensismentioning
confidence: 99%
“…For example, the bark is used as a powerful astringent to treat diarrhea, heavy menstruation, nosebleeding, headache, stomachache, schistosomiasis, sores, and skin problems; the root is believed to cure malaria, blackwater fever and gonorrhea [6,24,28,35,36]. Research studies reveal promising results concerning their antibacterial [37][38][39], antifungal [38], anthelmintic [40,41], and HIV-1 reverse transcriptase inhibitory properties [38] ( Table 1). At the environmental level P. angolensis is able to establish nitrogen-ixing symbiosis with rhizobium bacteria and therefore relevant for soil fertilization.…”
Section: No Studies Reportedmentioning
confidence: 99%
“…Pterocarpus angolensis DC Antischistosomal [90] RAPD [79,80] Stem, stem bark, leaves: anthelmintic [40] Seeds: antibacterial [91] Stem bark: antibacterial and anti-inlammatory; lack of mutagenicity [92] Stem bark, leaves: anthelmintic, antibacterial, and cytotoxic [41] Antibacterial [93] Stem bark: antibacterial; epicatechin and derivatives identiied [37] Stem bark: antibacterial; leaves, stem bark: antifungal, HIV-1 reverse transcriptase inhibitory [38] Leaves, stem bark: anti-inlammatory [94] Stem bark, roots: antibacterial; tannins and saponins identiied [39] Colophospermum mopane (Benth. )…”
Section: No Studies Reportedmentioning
confidence: 99%